The Process of Creation and Consolidation Committees for Hydrographic Basin Management Water Resources (Revista Brasileira Multidisciplinar, 2011)
Water is among the most precious goods in Earth's environmental heritage, however, the economic activities have caused the contamination and degradation of surface and underground springs. Consequently, emerges the need to reconcile the development and the management of natural resources. Several national and international conferences have been taken place to spread this idea. In Brazil, this new model of water resources management is beginning to be implanted, culminating in the approval of The State Water Resources Policy and, later, in the National Water Resources Policy. This legislation takes the river basin as a regional unity of water planning and management. The objective of this work is to present the evolution of the process of organization and creation of river basin committees. Literature search as well as documentary analysis (minutes, decisions) were used as research methodology. The experience of basin committees is considered an innovation for considering deliberative groups with effectively deliberative actions, incorporating guiding principles favoring shared management, taking as a support basis decentralization, integration and participation in the destiny of water resources in each region of the river basin. However, it is also necessary to intensify the involvement of users and other segments of society so that these groups can really work as "Water Parliament".
Keywords: Water Management; River Basin Committees; Watershed.